Impact of Climate Change on Temperate and Alpine Grasslands in China during 1982–2006 - Xiangjin Shen; Binhui Liu; Guangdi Li; Daowei Zhou (Advances in Meteorology)
Based on GIMMS NDVI and climate data from 1982 to 2006, this study analyzed the impact of climate change on grassland in China. During the growing season, there were significant effects of precipitation on the growth of all the grassland types (P<0.05), except for meadow vegetation. For the air temperatures, there existed asymmetrical effects of maximum temperature (Tmax) and minimum temperature (Tmin) on grassland vegetation, especially for the temperate grasslands and alpine steppe. The growing season NDVI correlated negatively with Tmax but positively with Tmin for temperate grasslands. Seasonally, these opposite effects were only observed in summer. For alpine steppe, the growing season NDVI correlated positively with Tmax but negatively with Tmin, and this pattern of asymmetrical responses was only obvious in spring and autumn. Under the background of global asymmetric warming, more attention should be paid to this asymmetric response of grassland vegetation to daytime and night-time warming, especially when we want to predict the productivity of China’s grasslands in the future.